 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```

```
7 months ago

```							 Dear student  put y = 0then you will get  f(0) ( 1 + f(x)) = 0 In case of any difficulty, Please feel free to ask again
```
7 months ago Saurabh Koranglekar
10233 Points
```							Dear studentAssume y = 0 to simplify the given equation and determine requiredRegards
```
7 months ago
```							Dear student, above answer is wrong. Correct answer is:On putting y=0, we see that f(0)(1+f(x))= 0Since f(x) is non constant, f(0)= 0Now, we can writef(x+y)-f(x)= f(y)(1+f(x))Or Lt y tends to 0 [f(x+y)-f(x)]/y = (1+f(x))*Lt y tends to 0 [f(y)-f(0)]/(y-0)Or f'(x)= f'(0)(1+f(x))= k(1+f(x))This differential equation can be easily solved by integrating as∫f'(x)dx/(1+f(x))= ∫kdxOr ln(1+f(x))= kx+cOr f(x)= Ae^kx-1Put x=0 to get f(0)= A-1Or A=1So, f(x)= e^kx - 1KINDLY APPROVE :))
```
7 months ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions